The Development of Social Responsibility among Students in School: the Social Test Method - Harlanova, Elena; Shirochenkova, Natalia; Yalakaeva, Oxana; Ulyanova, Liubov (SHS web of conferences, 2019)
In the conditions of unstable modern community development we should secure our future. Thus, the issue of social responsibility among both individuals (citizens, representatives of different professions), and collective subjects (corporations, governments, states) becomes more and more relevant. In this article, taking into account the experience of Russian and foreign scientists, the methodology of the activity approach, social and active education and theories of positive action of the youth, we may reveal the potential of the social test method in the development of social responsibility among secondary school students. The peculiar feature of this method being applied consists in ensuring the students’ voluntary participation in socially important activities. Moreover, these activities include the following discussion and feedback concerning their social responsibility (its value bases, the ways of demonstration and implementation, the effect on the participants and people around them) together with the consistently increasing authorship and social interaction experience in the course of analyzed activity.